Impact of milk feeding regimens on growth, intake, efficiency, and costs in pre-weaned crossbred calves - VIKAS, GAMIT; RAKESH, MODI; PRIYAM, AGRAVAT; PRAVINCHANDRA, LUNAGARIYA; KISHANKUMAR, WADHWANI (The Indian Journal of Animal Sciences, 2024)
The high milk (20% of weight) feeding in initial life is beneficial for growth, feed efficiency, and welfare of calves. The experiment aimed to evaluate the impact of different milk-feeding regimens on the growth, intake, physiological responses, blood and faeces attributes, feed efficiency, and feeding cost in crossbred calves. Thirty (n=30) healthy pre-weaned crossbred calves (75% HF × 25% Kankrej) were divided into five groups using a completely randomized design. The calves were fed milk 10% of body weight (T1); 4 L/day during the entire experiment (T2); 6,4,2 L/day during 2-6, 7-9, and 10-13 weeks of age (T3); and early weaning protocols 7, 5 L/day during 2-6, and 7-9 weeks of age (T4); as well as 8, 4 L/day during 2-6, and 7-9 weeks of age (T5), respectively after an adaptation of seven days. The feeding of concentrate, dry, and green fodder was common in all groups. The effect of milk-feeding regimens on body weight, body measurements, intake, and feed efficiency were non-significant. The evaluation of physiological responses, faecal consistency score, and blood haematology indicated that it was safe to feed different milk regimens. The milk feeding up to 13 weeks of age (T1, T2, T3) significantly lowered the cost of feeding for weight gain than the early weaning protocol (T4, T5). Among them, the feeding of T3 regimen was economical for weight gain without affecting the growth performance, feed efficiency, and health attributes of crossbred calves.